Global Academic Publishing Challenges and National Policy Adaptation: Azerbaijan’s Strategic Options for Equitable Access to Scientific Knowledge - Mammadov, Sadig; Asadov, Arif; Ahmadsoy, Narmin; Namazov, Ismayil (My University, 2026)
The main objective of this Capstone project is to investigate the causes of the publishing crisis and its impact on the accessibility of scientific knowledge. The study finds that scientific publishing is highly concentrated within the global system among a few major publishers. Publishers such as Elsevier, Springer Nature, Wiley, Taylor & Francis, and SAGE have created a system which has led to various problems within scientific publishing, such as a lack of competition, network effects, platform capitalism, lack of antitrust regulations, and the unpaid exploitation of academic labour. The research used a qualitative methodology. Semi-structured interviews were conducted with six experts on scientific publishing in Azerbaijan, as well as reviewing local and international scholarly literature on the topic. Each interview was anonymized using the codes R1-R6, and the results were analysed. The results show that the problem exists not only globally, but also at the national level of science policy, universities, and scientists in Azerbaijan. Current assessment systems put scholars in a dependent position to a limited range of international indexing systems. This reliance reduces the ability of indigenous journals to flourish, diminishes the ideals of open science, and facilitates the transfer of knowledge to commercial platforms without compensation. Three policy options are suggested: setting transparency and cost caps for APC payments; modifying academic evaluation and attestation systems; and enhancing open access publishing and collaborative research platforms in universities. The analysis suggests that the most realistic and institutionally manageable policy change in the short term is to revise academic assessment, promotion, and attestation processes.
Keywords: academic publishing crisis; Open Access; APC; academic labour; oligopoly; antitrust regulation; research policy